Rational designing of glyco-nanovehicles to target cellular heterogeneity. Issue 11 (3rd February 2021) - Jain, Prashant; Shanthamurthy, Chethan D.; Chaudhary, Preeti Madhukar; Kikkeri, Raghavendra
Abstract : Heparan sulfate oligosaccharide based nanovehicle greatly enhance the selective targeting of cancer cells in tumor microenvironment. Abstract : The aberrant expression of endocytic epidermal growth factor receptors (EGFRs) in cancer cells has emerged as a key target for therapeutic intervention. Here, we describe for the first time a state-of-the-art design for a heparan sulfate (HS) oligosaccharide-based nanovehicle to target EGFR-overexpressed cancer cells in cellular heterogeneity. An ELISA plate IC50 inhibition assay and surface plasma resonance (SPR) binding assay of structurally well-defined HS oligosaccharides showed that 6- O -sulfation (6- O -S) and 6- O -phosphorylation (6- O -P) of HS tetrasaccharides significantly enhanced EGFR cognate growth factor binding. The conjugation of these HS ligands to multivalent fluorescent gold nanoparticles (AuNPs) enabled the specific and efficient targeting of EGFR-overexpressed cancer cells. In addition, this heparinoid-nanovehicle exhibited selective homing to NPs in cancer cells in three-dimensional (3D) coculture spheroids, thus providing a novel target for cancer therapy and diagnostics in the tumor microenvironment (TME).